EFFECT OF LONG-TERM EXPOSURE TO ENDOSULFAN ON BLOOD CELL COUNT IN CHANNA GACHUA - Deshmukh, D. R.; Sonawane, S. R. (Journal of Indian Fisheries Association, 2007)
In the present investigation, live specimens of Channa gachua were exposed to sublethal concentrations, i.e., 0.0017 and 0.00087 ppm, of endosulfanÂ for a period of 60 days. After the completion of 60 days, red and white bloodÂ corpuscles were counted from control as well as experimental fishes. Keywords: Channa gachua, endosulfan, blood cells